2013
DOI: 10.1177/2041731413503357
|View full text |Cite
|
Sign up to set email alerts
|

Silica-based mesoporous nanoparticles for controlled drug delivery

Abstract: Drug molecules with lack of specificity and solubility lead patients to take high doses of the drug to achieve sufficient therapeutic effects. This is a leading cause of adverse drug reactions, particularly for drugs with narrow therapeutic window or cytotoxic chemotherapeutics. To address these problems, there are various functional biocompatible drug carriers available in the market, which can deliver therapeutic agents to the target site in a controlled manner. Among the carriers developed thus far, mesopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
180
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(189 citation statements)
references
References 136 publications
(297 reference statements)
3
180
0
6
Order By: Relevance
“…Based on the previous reports, various methods have been employed such as hydrolysis, microemulsions, and co-precipitation. Meanwhile, the Fe3O4/SiO2 nanocomposites have been fabricated via coprecipitation method [1], [15], [23], [24]. In this work, we exploited a simple coprecipitation method at room temperature which easier to control the particle size of the samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous reports, various methods have been employed such as hydrolysis, microemulsions, and co-precipitation. Meanwhile, the Fe3O4/SiO2 nanocomposites have been fabricated via coprecipitation method [1], [15], [23], [24]. In this work, we exploited a simple coprecipitation method at room temperature which easier to control the particle size of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the SiO2 nanoparticle has an amorphous phase, and it can be commercially produced as silica gel, fume-silica, and so forth. Several applications of SiO2 nanoparticles for examples such as medical purposes [22][23][24], as additives for rubber and plastics [25][26][27], as fillers for composite construction concrete [28][29][30], as stabilizers and agents drug delivery and theranostics [23,31], and as a heavy metal absorbent material in a water filter [14], [22].…”
Section: Introductionmentioning
confidence: 99%
“…Copolymerization of NIPAM with different monomers thus allows tuning of the properties especially LCST of PNIPAM according to the requirements of the applications under investigation. There is increased interest in hybrid thermoresponsive DDS as several studies reported their synthesis and testing for the delivery of various drugs in different environments and physiological conditions, including dermal drug delivery and also their use in dermocosmetic applications [10]. For the preparation of hybrid thermosensitive DDS, the thermoresponsive polymer needs to be anchored on a solid support.…”
Section: Introductionmentioning
confidence: 99%
“…This refers to pores acting as passages between the external and internal surfaces of a solid, allowing material to pass into, through, or out of the solid [16]. The possibility of using mesoporous materials such as Santa Barbara Amorphous-15 (SBA-15) or Mobile Crystalline Matter-48 (MCM-48) and some metal organic frameworks as drug carriers and controlled release systems has been discussed [18,19]. Mesoporous materials are essentially prepared through the formation of silica around template micelle assemblies followed by removal of the template using appropriate methods such as calcination and solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%